PENINGKATAN KUALITAS PROSES DAN HASIL BELAJAR BIOLOGI PRONBIOTEK DENGAN MODEL EXPRIENTAL LEARNING SISWA KELAS XII IPA2 SMA NEGERI 1 PASUI - Kasmiati, Kasmiati (Lembaga Penelitian Mahasiswa Penalaran UNM, 2020)
The background of this research was carried out because of the importance of efforts to improve learning achievement in biology through several methods or optimal learning strategies. The purpose of this study was to determine the improvement in the quality of the process and learning outcomes that have an impact on learning achievement in biology after applying the principles of biotechnology with the experiential learning model of class XII IPA2 students of SMA Negeri 1 Pasui. This research is a classroom action research which investigates student factors, teacher factors and the quality of the biology learning process and outcomes. The research location is SMA Negeri 1 Pasui, Enrekang Regency, class XII IPA2, with a total of 21 students in the even semester of the 2016-2017 school year. The implementation of the action consists of two cycles followed by evaluation and reflection activities. The results of the study show that the application of biotics with the experiential learning model can improve the quality of the process and student learning outcomes. Student responses are very positive and student learning outcomes improve each cycle.Keywords: prinbiotech, experiential learning, process quality and learning outcomes